(untitled) (Biological Sciences - PJSIR, 1995)
The air dried seeds of Sapodilla plum contain moisture 6.0%, hulls 51.7%, and kernels 42.3%. The hulls contain oil 0.45%, ash0.77%, protein 2.05% (indefattedhulls) whereasthekernels containoils 19.8%,ash6.50% and protein 16.93% (in defatted kernels). The fatty acid composition of dark yellow coloured hull oil is lauric acid (5.38%), myristic acid (3.30%), palmitic acid (26.14%), stearic acid (9.3%), oleic acid (39.46%), linoleic acid (13.93%), and linolenic acid (2.36%)whereas lightyellowcolouredkernel oilcontainspalmiticacid(17.24%),stearicacid (10.14%), oleic acid (60.40%), linoleic acid (9.30%), linolenic acid (2.03%) and an unknown fatty acid (0.89%) respectively. The unsaponifiable matter is determined as sterols (23.7% and 20.1%) alcohols (32.5% and 33.3%) hydrocarbons (43.8% and46.6%) in hull andkernel oil respectively. The hydrocarbons CI5 -C29 (inkernel oil), alcohols Cl2 -CIS (in hull oil) and CI6 -CIS (in kernel oil) respectively have been separated, identified and characterized by the application of thin layer and gas liquid chromatography. Palmityl and oleyl alcholos are found to predominate in both the oils.